The Rasch Analysis Of Perceived Wellness Survey For Senior High School Students In Indonesia - Herdi, Herdi; Yuningsih, Ayu Tri (Psikopedagogia, 2023)
A measurement tool for the well-being of high school students in Indonesia is needed. This study aims to adapt and test the psychometric properties of the Perceived Wellness Survey Full Length (PWS-FL) and the new Perceived Wellness Survey Short Form (PWS-SF) for high school students within the Indonesian cultural context. The study is quantitative, employing the Rasch model. The sampling method used is purposive sampling, involving 360 high school students. The study instruments used are the Perceived Wellness Survey Full Length (PWS-FL) and the new Perceived Wellness Survey Short Form (PWS-SF).  The results of the study show that the PWS-FL and PWS-SF are valid and reliable using the Rasch model. The data obtained with these instruments can be used as a basis for developing guidance and counseling programs to enhance the well-being of high school students.